PENGUATAN NILAI-NILAI RELIGIUS SEBAGAI KARAKTER SISWA MELALUI STRATEGI PEMBELAJARAN PAI DI MTS ASSA’ADAH I BUNGAH GRESIK - Nur Hasib Muhammad; M. Ali Musyafa’ (Kuttab : Jurnal Ilmu Pendidikan Islam, 2022)
Islamic religious education learning strategies are techniques, procedures, and learning models used so that the teachings of the Islamic religion can be studied, understood, internalized, and practiced in everyday life. This is nothing but an effort to shape the religious character of students in order to create a religious society. This study aims to describe; planning PAI learning strategies in shaping religious characters, implementing PAI learning strategies in shaping religious characters, and describing the impact of PAI learning strategies in shaping students' religious characters at MTs Assa'adah I Bungah Gresik. The research method in this study uses a qualitative type with a case study approach. This study succeeded in finding that: 1) PAI learning strategies in shaping students' religious character in preparing lesson plans and evaluating learning; 2) The implementation of strengthening religious values as student characters is carried out through strategies for understanding, habituation, and exemplary religious values; 3) The religious values developed include worship, the value of the spirit of jihad, the value of trust and sincerity, the value of morals and discipline, and the value of exemplary.